The traditional building technology against cold and its cultural significance of Daur - Yina, Qiao; Rattanarungsikul, Phuvanart (วารสารรัฐศาสตร์รอบรู้และสหวิทยาการ, 2025)
The Daur people are ethnic minorities in northern China, traditionally residing in cold, high-latitude regions where winter temperatures often drop to 40 °C or even lower. Under such long and harsh winter conditions, the Daur people have developed a unique set of traditional building techniques for surviving in the cold weather. These techniques entirely use natural resources, adapting to frigid environments through site selection, materials, structural design, and internal layout. For example, houses are built on sheltered terrain facing south to utilize solar heat; walls are constructed with local wood and earth; straw covers the roofs to enhance insulation; the indoor heated brick system provides warmth and optimizes heat distribution. These cold-resistant techniques not only meet living needs but also carry rich cultural significance, reflecting the Daur people's wisdom in adapting to nature, their core values of family harmony, and the symbolic identity of the ethnic group. However, as modernization accelerates, these traditional buildings are gradually being replaced by modern structures, posing a risk of losing their cold-resistant techniques and cultural significance. This article systematically analyzes the cold-resistant techniques and cultural significance of Daur traditional architecture, proposing specific recommendations for protection and inheritance and providing insights for cultural heritage preservation and modern architectural design.